Description of the Migration of Karakalpaks to Baisyn in Historical Songs - Turdiev Bakhtiyar (Zien Journals, 2022)
The article describes the historical events in the historical song "To Baisyn". This song describes the disintegration of the people from Khorezm after Genghis Khan's conquest of the Khorezmshahs' capital, Urgench. Little is known about the life of the Karakalpaks during Genghis Khan's defeat of Khorezm, but there are many invaluable folklore works of this period
Keywords: Karakalpaks; historical songs; disintegration